Implementation of the Death Penalty for Corruptors in Indonesia - Reski Nofrialdi (Siber Nusantara Research, 2024)
The death penalty for corruptors in Indonesia is a controversial topic that has sparked debates among the public. Proponents argue that it serves as a deterrent for those engaging in corrupt practices, while opponents believe that it goes against human rights and does not address the root causes of corruption. As the government continues to grapple with this issue, the effectiveness and ethical implications of implementing such a severe punishment remain under scrutiny. While some argue that the death penalty is necessary to send a strong message against corruption, others believe that it is a violation of basic human rights. Additionally, many question whether the death penalty actually addresses the systemic issues that allow corruption to thrive in the first place. As the debate continues, it is crucial for policymakers to consider all perspectives and weigh the potential consequences of implementing such a drastic measure. Ultimately, finding a balance between justice and human rights is paramount in addressing corruption in Indonesia.